The Use of Benchmarking in the Cost Optimization of Medical Services - Macuda , Małgorzata; Łuczak , Krzysztof (Studia Oeconomica Posnaniensia, 2014)
Management accounting increasingly uses modern management methods, which includes benchmarking. This article presents the possibility of using benchmarking for the cost optimization of medical services for different diagnosis-related groups (DRG). The article presents empirical research on the actual cost of medical services based on selected DRG.